1976
DOI: 10.2466/pms.1976.43.3.719
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Style, Hemispheric Specialization, and Tested Abilities of Transsexuals and Nontranssexuals

Abstract: Tests on which the 12 males and the 8 male transsexuals differed significantly and might be useful to clinicians for differentiation were the Embedded-figures Test, the Porteus Mazes, and the O'Connor Finger Dexterity Test. Sex differences emerged on the Embedded-figures Test and the first half of the dexterity test. There were no significant differences between 12 males and 14 females or males and 8 transsexuals on conjugate lateral eye movement, eye dominance, Digit Span, and Digit Symbol. Embedded-figures T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In general, men tend to process verbal stimuli in a more lateralized way than women; they also show a weaker righthand preference (McGlone 1978;Kimura 1996). Several studies of transsexual subjects have shown a sex-atypical performance in visuospatial (La Torre et al 1976;van Goozen et al 2002) and language functions (Cohen-Kettenis et al 1998), although some were unable to reproduce these patterns (Haraldsen et al 2005). A sex deviant performance has been described even prior to cross-sex hormone therapy (van Goozen et al 2002), further emphasizing an impact of biologically determined factors, such as sex-atypical cerebral programing, in gender dysphoria.…”
Section: Introductionmentioning
confidence: 99%
“…In general, men tend to process verbal stimuli in a more lateralized way than women; they also show a weaker righthand preference (McGlone 1978;Kimura 1996). Several studies of transsexual subjects have shown a sex-atypical performance in visuospatial (La Torre et al 1976;van Goozen et al 2002) and language functions (Cohen-Kettenis et al 1998), although some were unable to reproduce these patterns (Haraldsen et al 2005). A sex deviant performance has been described even prior to cross-sex hormone therapy (van Goozen et al 2002), further emphasizing an impact of biologically determined factors, such as sex-atypical cerebral programing, in gender dysphoria.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study found that estrogen treatment in MFs affected verbal memory but not verbal or visuospatial ability (Miles, Green, Sanders, & Hines, 1998). Finally, it has been found that hormonally treated MFs were similar in spatial ability performance to control women but different from control men (La-Torre, Gossmann, & Piper, 1976).…”
mentioning
confidence: 97%
“…After extensive statistical analysis and a complex process of meaning making (see Alac ˇand Hutchins 2004;Dumit 2004) out of the images on the visual monitor, most studies determine that there are similarities in brain structures and activation patterns between transsexuals prior to hormone therapy (HT) and subjects who share their gender identity. Changes after HT are usually found not to be attributable to the differences in brains prior to HT (see Luders et al 2009;Rametti et al 2011;Zhou et al 1995;Van Goozen et al 2002;Swaab 2004;Garcia-Falgueras and Swaab 2008;Miles, Green, and Hines 2006;La Torre, Grossman, and Piper 1976;Haraldsen et al 2003;Prince 2005;and Sullivan 2008). The results and conclusion of inherent transsexuality, sans the hormonal transition aspect, mirror Simon LeVay's (1993: 120-24) earlier work in which he located structural and functional differences between self-identified gay men's brains and those of heterosexual men, noting that the structures were similar to those of presumably heterosexual women.…”
Section: Brain Imagingmentioning
confidence: 99%